The Influence of Entrepreneurial Education and Training on Work Readiness of Vocational Beauty and Cosmetology Graduates - Astuti, Murni; Giatman, Giatman; Syah, Nur Hasan (Fakultas Pariwisata dan Perhotelan Universitas Negeri Padang, 2024)
This research aims to see the influence of education and entrepreneurship training on the work readiness of students at the Department of Beauty and Cosmetology of 2022. The research method used is quantitative research with an ex-post facto design. The population of this research is all students of the Department of Beauty and Cosmetology of 2022, who are the data sample. Data collection was carried out through tests and questionnaires. Data analysis uses simple regression analysis and multiple regression analysis. The research results show that education has a positive influence on work readiness with a coefficient of determination value of 0.066 (Y=59.371+0.225X1). Likewise, entrepreneurship training also has a positive influence on work readiness with a coefficient of determination value of 0.065 (Y=68.596+0.526X2). Apart from that, together, education and entrepreneurship training also have a positive effect on work readiness with a coefficient of determination of 0.125 (Y=52.381+0.214X1+0.500X2). These findings indicate that both education and entrepreneurship training have a significant role in preparing graduates to face the demands of the world of work, especially in the dynamic and competitive beauty industry. The implications of this research can contribute to the development of vocational education curricula that are more relevant to the needs of the job market and provide recommendations for educational institutions and the government in increasing the effectiveness of entrepreneurship education and training programs.